The Dawns of Justice. From Legalized Impunity to Judgments as Policy of State - Leavi, Carlos (Facultad de Periodismo y Comunicación Social, 2017)
At the heath of the 1990s, when the institutional channels were closed to demand justice, the judgments for the truth, the popular judgments and the escraches constituted the principal forms of participation and extension of the democracy. Since the author raises, whereas the symbolic significance of the judgments for the truth was what allowed to generate the cultural and juridical conditions for the production of the judgments that were realized after the derogation of the laws of Punto Final and Obediencia Debida and of the pardon, the popular courts and the escraches extended the presence of this symbolic sentences in the territory of the public spaces.